1996
DOI: 10.1002/1529-0131(199610)9:5<391::aid-anr1790090508>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Health outcome improvements in patients with systemic lupus erythematosus using two telephone counseling interventions

Abstract: Objective. To examine the effectiveness of two telephone intervention strategies for improving the health outcomes of patients with systemic lupus elythema-tosus (SLE). Methods. Fi&-eight SLEpatients were randomlyas-signed to receive a 6-month telephone counseling intervention using either a treatment counseling (TC) or symptom monitoring (SM) strateg. Health outcomes were assessed using the Fatigue Severity Scale (FSS) and the Arthritis Impact Measurement Scales 2 (ALMS2). Results. At the 6-month followup, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 33 publications
(20 reference statements)
4
71
0
1
Order By: Relevance
“…In this trial, we demonstrated that self-efficacy could be enhanced by our intervention and that it was a key predictor of mental health status and fatigue outcomes. These results are consistent with results of another randomized, controlled trial of counseling for SLE patients in a group setting, which demonstrated significant improvements in psychological status but not in physical functioning and social support (23). That trial did not involve a partner but was similar to our trial, in that the counselor targeted 6 patient behaviors: self-care activities in managing fatigue, patient's communication skills, removing barriers to medical care, medication self-management, symptom monitoring, and stress control methods.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this trial, we demonstrated that self-efficacy could be enhanced by our intervention and that it was a key predictor of mental health status and fatigue outcomes. These results are consistent with results of another randomized, controlled trial of counseling for SLE patients in a group setting, which demonstrated significant improvements in psychological status but not in physical functioning and social support (23). That trial did not involve a partner but was similar to our trial, in that the counselor targeted 6 patient behaviors: self-care activities in managing fatigue, patient's communication skills, removing barriers to medical care, medication self-management, symptom monitoring, and stress control methods.…”
Section: Discussionsupporting
confidence: 89%
“…A clinical trial of person-centered telephone counseling demonstrated significant improvements in psychological status but not in physical functioning in 15 patients with SLE (22). In another trial conducted by the same group of investigators, 58 patients with SLE were randomized to receive either telephone counseling or symptom monitoring, and significant improvement in physical function and social support was demonstrated in the counseling group (23). In contrast, a randomized clinical trial of brief supportive-expressive group psychotherapy in 133 patients with SLE from 9 clinics across Canada showed no significant benefits in psychological distress, medical symptoms, health care costs, and quality of life (24).…”
mentioning
confidence: 99%
“…Six of the eight RCTs compared the telephone intervention with routine care, 26,28,32 -35 one trial employed symptom monitoring as the control condition 25 and the final trial compared telephone CBT to telephone supportive emotion-focused therapy. 27 Two trials 26,35 had three intervention arms.…”
Section: Resultsmentioning
confidence: 99%
“…Arthritis self-management education delivered by small-group, home study, computer, or internet modalities have demonstrated significant improvements in health distress, self-reported global health, and activity limitation, with trends toward improvement in self-efficacy and mental stress management [20,[36][37][38][39][40][41][42][43][44][45]. However, African Americans and women are still disproportionately impacted by lupus [46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%